Transcriptomic analysis of Chinese yam (Dioscorea polystachya Turcz.) variants indicates brassinosteroid involvement in tuber development - Riekötter, Jenny; Oklestkova, Jana; Muth, Jost; Twyman, Richard M.; Epping, Janina (Frontiers in Nutrition, 2023)
Dioscorea is an important but underutilized genus of flowering plants that grows predominantly in tropical and subtropical regions. Several species, known as yam, develop large underground tubers and aerial bulbils that are used as food. The Chinese yam (D. polystachya Turcz.) is one of the few Dioscorea species that grows well in temperate regions and has been proposed as a climate-resilient crop to enhance food security in Europe. However, the fragile, club-like tubers are unsuitable for mechanical harvesting, which is facilitated by shorter and thicker storage organs. Brassinosteroids (BRs) play a key role in plant cell division, cell elongation and proliferation, as well as in the gravitropic response. We found that BRs can influence tuber shape in Chinese yam by regulating the expression of genes involved cell expansion. We collected RNA-Seq data from the head, middle and tip of two tuber shape variants: F60 (long, thin) and F2000 (short, thick). Comparative transcriptome analysis of F60 vs F2000 revealed 30,229 differentially expressed genes (DEGs), 1393 of which were differentially expressed in the growing tip. Several DEGs are involved in steroid/BR biosynthesis or signaling, or may be regulated by BRs. The quantification of endogenous BRs revealed higher levels of castasterone (CS), 28-norCS, 28-homoCS and brassinolide in F2000 compared to F60 tubers. The highest BR levels were detected in the growing tip, and CS was the most abundant (439.6 ± 196.41 pmol/g in F2000 and 365.6 ± 112.78 pmol/g in F60). Exogenous 24-epi-brassinolide (epi-BL) treatment (20 nM) in an aeroponic system significantly increased the width-to-length ratio (0.045 ± 0.002) compared to the mock-treated plants (0.03 ± 0.002) after 7 weeks, indicating that exogenous epi-BL produces shorter and thicker tubers. This is the first report demonstrating the role of BRs in D. polystachya tuber shape, providing insight into the role of plant hormones in yam storage organ development. Our data can help to improve the efficiency of Chinese yam cultivation, which could provide an alternative food source and thus contribute to future food security in Europe.